A cultura em questões - Caleb Faria Alves (Ciências Sociais Unisinos)
The service sector and public policies are increasingly making use of the concept of culture. Management courses, government programs and social research directly focusing on this field proliferate. They seek support, however, in investigative polls. This article addresses, comparatively, the content of this term – explicit or not –in some of these surveys in Brazil and Latin America. Our first goal is to highlight the assumptions used to qualify and measure the consumption of cultural goods contained in the polls – in other words, to which extent this consumption is linked to culture itself –, identifying whether culture is treated as an autonomous field or as an accessory to concerns that are external to it. An important parameter is to highlight how cultural preferences are treated as ele- ments of distinctive imposition and not just as a possibility generated by income. Then we assess how the public and private sectors are articulated in the production and use of these data, keeping the focus on definitions. The article also discusses the academia and recent redefinitions of the role of intellectuals.